Hubungan Keanekaragaman Mesofauna Tanah dengan Kadar Bahan Organik di Hutan Sekunder Desa Candikuning - Silva, Lizeti Frania Da; Kesumadewi, Anak Agung Istri; Atmaja, I Wayan Dana (Agrotrop : Journal on Agriculture Science, 2023)
Relationship of Soil Mesofauna Diversity with Organic Little in Secondary Forest in Candikuning Village. Soil mesofauna play important role in maintaining and supporting soil fertility of natural forest. Their population, diversity, and function influenced by organic residues and inhibit by disturbance on the habitat, i.e., forest fragmentation. A field study to confirm the differences of soil mesofauna diversity and its relation to organic matter content among fragmented secondary natural forest in Candikuning village had done on February – April 2022.  Study site was four fragmented secondary forest in Candikuning Village, i.e., Botanical Garden in Bedugul, secondary Geothermal natural forest, secondary natural forest impacted by short-cut development, and Village Binggo forest. Every 15 composite soil sample and organic residue had taken from minipit on each secondary natural forest followed by 3 replications. Soil mesofauna was extracted using berlesse-tullgren and lighted by 45 watt led lamp for 48 hours. Morphological identification of the soil mesofauna showed that 5 orders, 12 families, 15 genera, and 15 species were found on the study site. Soil mesofauna dominance index in shortcut forest, Bedugul botanical garden forest, and geothermal forest was low (D = <0.3), which is between 0.05-0.22. The soil mesofauna diversity index in shortcut forest, Bedugul botanical garden forest, and geothermal forest was medium (H` = 1-3), which is between 1.64-2.30. The evenness index of the soil mesofauna at all research sites was high (E = > 0.6), which was between 0.70-0.98. The correlation of organic matter with soil mesofauna only significantly positive to Hemiptera in Geothermal Forest.